Toxic mechanism of cadmium exposure on cardiac tissue - Novelli, Ethel Lourenzi Barbosa [UNESP]; Marques, S. F G [UNESP]; Almeida, J. A. [UNESP]; Diniz, Y. S. [UNESP]; Faine, L. A. [UNESP]; Ribas, B. O. [UNESP] (My University, 2000)
The presence of toxic substances in the workplace environment requires systematic evaluation of exposure and health status in exposed subjects. Cadmium is a highly toxic element found in water. Although free mediated cellular damage and reactive oxygen species (ROS), had been theorized as contributing to the cadmium mechanism of toxicity, and recent investigations have established that free radicals may be important contributors to cardiac dysfunction, there is little information on the effect of cadmium exposure on markers of oxidative stress in cardiac tissue. Cadmium exposure (Cd2+ - 100 mg/1-from CdCl2) in drinking water, during 15 days, significantly increased lipoperoxide and decreased the activities of superoxide dismutase and glutathione peroxidase. No alterations were observed in catalase activity in heart of rats with cadmium exposure. We also observed decreased glycogen and glucose concentration and increased total lipid content in cardiac tissue of rats with cadmium exposure. The decreased activities of alanine transaminase and aspartate transaminase reflected decreased metabolic protein degradation, and increased lactate dehydrogenase activity was related with increases in capacity of glycolysis. Since the metabolic pathways were altered by cadmium exposure, we can conclude that Cd2+ exposure induced ROS and initiate some series of events that occur in the heart and resulted in metabolic pathways alterations.
Keywords: alanine aminotransferase; aspartate aminotransferase; cadmium; catalase; drinking water; glutathione peroxidase; reactive oxygen metabolite; superoxide dismutase; animal experiment; animal tissue; cardiotoxicity; cell damage; concentration response; controlled study; enzyme activity; lipid peroxidation; male; metabolism; nonhuman; occupational exposure; oxidative stress; pathophysiology; protein degradation; rat; water contamination; Animalia